DETERMINANTS OF SUSTAINABILITY OF THE MILITARY FROM THE ARMED FORCES OF UKRAINE TO COMBAT STRESS - Inesa V. Harkusha; Valery I. Kaiko (Alfred Nobel University Publisher, 2019)
The article deals with the determinants of resistance to the combat stress of the military from the Ukrainian Armed Forces, which contribute to highly productive activity in the extreme space. The professional activity of many people takes place in extreme conditions ‒ especially of the military of the Armed Forces of Ukraine. Each stressful situation in a professional or other activity causes a complex of assessment processes, agreements, and settlement when a person interacts with stressors. Stress resistance can be distinguished as a personality trait that provides a harmonious relationship between all components of mental activity in an emotional situation and, thereby, contributes to the successful implementation of actions. There are three types of a person's relationship to himself in a situation of stress caused by extreme conditions. The first is a primitive-selfish attitude toward oneself as a «victim». The second type can be called the objectively individualistic one. The third type, allows attitude to oneself as one of a number of people, most conducive to effective activity under stress. The level of self-esteem is complexly linked with stress. Individuals with fairly high self-esteem, as a rule, do not respond to emotionally severe or stressful stimuli. People with low self-esteem have a high level of fear or anxiety under the threat of stress and see themselves as having inadequate abilities to withstand it. The ability to cope with stress depends on how well a soldier is prepared for it, on the attitude to the daily requirements that are imposed by life. The ability to adapt is not only an individual, but also a person's personality trait. Adaptive abilities depend on the psychological characteristics of the individual, which are determined by the possibility of adequate regulation of physiological states.